Linking global CGE models and sectoral analysis to evaluate the impact of trade openness in service sector towards Indonesia agricultural and agroindustry - Widyastutik Widyastutik; Birka Septy Meliany; Syarifah Amaliah; Hotsawadi; Amzul Rifin (Economies, 2025)
Agriculture is the primary sector sustaining the Indonesian economy. However, appropriate policies are also required to support the service sector. Therefore, this study aims to analyze two central policies: the impact of trade openness and the role of the service sector on agriculture and agro-industry in Indonesia. A Computable General Equilibrium (CGE) model with 2016 input-output tables cover 141 regions and 65 sectors based on the Global Trade Analysis Project (GTAP) Version 10 database. The results show that trade openness in the services sector significantly improves the performance and quality of service provision. The improved performance of the services sector will, in turn, encourage increased production in the agricultural and agro-industrial sectors, which rely heavily on service inputs in the production process. This suggests that trade openness in the services sector is important to sustain the performance of the agricultural sector.
Keywords: 330; trade on services; computable general equilibrium (CGE) model; international trade; agricultural and agroindustry